Sex-ratios and work in Latin American households: Evidence from Mexico, Peru, Ecuador, Colombia, and Chile - Campaña, Juan Carlos; Giménez-Nadal, J Ignacio; Molina, José Alberto (Latin American Economic Review, 2021)
Abstract: We analyze the relationship between sex-ratios in the region of residence, and the time devoted to paid and unpaid work by couples in Mexico (2002, 2009, 2014), Peru (2010), Ecuador (2012), Colombia (2012, 2017) and Chile (2015). We find that sex-ratios are negatively related to the time devoted by women to paid work in Ecuador, and positively related to the time devoted by men to paid work in Mexico and Chile. In Colombia, sex-ratios are negatively related to the time devoted by men to unpaid work, while in Mexico and Peru they are negatively related to the time devoted by women to unpaid work. These results illustrate the importance of studying this topic in countries where the evidence is scarce, mainly due to limitations in the data.
Keywords: Business history in Latin America